NEURODEVELOPMENTAL DISORDERS IN CHILDREN WITH 22q11.2 DELETION SYNDROME AND RECOMMENDATIONS FOR PEDIATRIC FOLLOW UP - Cuturilo, Goran; Pavlovic, Zorana; Drakulic, Danijela (Medical Research, 2025)
SummaryNeurodevelopmental disorders are the most prevalent chronic diagnoses in pediatric primary care, with rising incidence and significant impact on cognitive, motor, social, and communication functioning. 22q11.2 deletion syndrome (22q11.2 DS)—the most common human microdeletion syndrome—presents with a broad spectrum of somatic and neurodevelopmental abnormalities. Nearly all individuals with 22q11.2 DS show neurodevelopmental difficulties, including delays in motor and speech milestones, cognitive impairments, and behavioral challenges. The disorder affects approximately 1 in 2,500 newborns and is also associated with congenital heart defects, palatal anomalies, hypocalcemia, and immunodeficiency. Neurodevelopmental manifestations typically begin in infancy with delayed motor and speech development and progress into school age with difficulties in learning, attention, and peer interaction. Intellectual disabilities are common, with a distribution skewed toward lower IQ scores. Children often exhibit a verbal-performance IQ discrepancy and may experience further cognitive decline in adolescence or adulthood. Over 40% of affected individuals meet criteria for autism spectrum disorder, attention-deficit/hyperactivity disorder, or both. They also have increased risks for psychiatric conditions such as anxiety, depression, and schizophrenia. Pediatricians, as primary care providers, play a critical role in early identification and long-term monitoring. Recommendations include routine developmental assessments, early interventions (e.g., speech and occupational therapy), and regular IQ and adaptive functioning evaluations, especially during educational transitions. Early diagnosis and individualized, multidisciplinary approaches are essential to improve developmental outcomes and quality of life in children with 22q11.2 DS.Keywords: 22q11.2 deletion syndrome, DiGeorge syndrome, neurodevelopmentaldisorders
Keywords: 22q11.2 deletion syndrome, DiGeorge syndrome, neurodevelopmental disorders